SubLinearForce: Fully Sublinear-Time Force Computation for Large Complex Graph Drawing - Meidiana, Amyra; Hong, Seok-Hee; Cai, Shijun; Torkel, Marnijati; Eades, Peter (IEEE transactions on visualization and computer graphics, 2024)
Recent works in graph visualization attempt to reduce the runtime of repulsion force computation of force-directed algorithms using sampling. However, they fail to reduce the runtime for attraction force computation to sublinear in the number of edges. We present the SubLinearForce framework for a fully sublinear-time force computation algorithm for drawing large complex graphs. More precisely, we present new sublinear-time algorithms for the attraction force computation of force-directed algorithms. We then integrate them with sublinear-time repulsion force computation to give a fully sublinear-time force computation. Extensive experiments show that our algorithms compute layouts on average 80% faster than the existing linear-time force computation algorithm, while obtaining significantly better quality metrics such as edge crossing and shape-based metrics.